Posttranscriptional clearance of hepatitis B virus RNA by cytotoxic T lymphocyte-activated hepatocytes. - Tsui, L V (1995)
Using transgenic mice that replicate the hepatitis B virus (HBV) genome, we recently demonstrated that class I-restricted, hepatitis B surface antigen-specific cytotoxic T lymphocytes (CTLs) can noncytolytically eliminate HBV pregenomic and envelope RNA transcripts from the hepatocyte. We now demonstrate that the steady-state content of these viral transcripts is profoundly reduced in the nucleus and cytoplasm of CTL-activated hepatocytes, but their transcription rates are only slightly reduced. Additionally, we demonstrate that transcripts covering the HBV X coding region are resistant to downregulation by the CTL. These results imply the existence of CTL-inducible hepatocellular factors that interact with a discrete element(s) between nucleotides 3157 and 1239 within the viral pregenomic and envelope transcripts and mediate their degradation, thus converting the hepatocyte from a passive victim to an active participant in the host response to HBV infection.